Peran Pembiasaan Salat Berjamaah dalam Internalisasi Karakter Religius Peserta Didik di SMP Jam’iyyatuttholibin - Hidayat Zainurrohim; Moh. Sakir; Ali Mutafi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study examines the role of congregational prayer habituation in internalizing students’ religious character at SMP Jam'iyyatut Tholibin. Congregational prayer serves not only as a form of worship but also as a strategy for instilling religious values through consistent practice. This field research employed a phenomenological approach with a qualitative descriptive method. Primary data were collected through interviews with the principal, Islamic Religious Education teachers, the vice principal for student affairs, and students, while secondary data were obtained from school documents and relevant literature. Data collection techniques included observation, interviews, and documentation, and the data were analyzed through reduction, presentation, and conclusion drawing, with validity ensured through source and technique triangulation. The findings show that the regular habituation of Duha and Dhuhr prayers, supported by Qur’an recitation, Asmaul Husna, and Morning Inspirational Stories (CIP), effectively strengthens students’ discipline, responsibility, worship obedience, humility, and solidarity. Although challenges such as limited student motivation and external environmental influences remain, continuous guidance, motivation, and teachers’ exemplary behavior effectively support the internalization process. Overall, integrating congregational prayer with complementary religious activities effectively promotes students’ religious character development.